Glucose priming effect on microbial intercellular metabolic flux diversity in a marine intertidal sediment - Tao Ji; Zhiao Xu; Lihong Wen; Yuxue Yang; Yue Wu; Xueqin Zhao; Ruilian Yao; Rulong Liu; Yunping Xu; Weichao Wu (PLoS ONE, 2025)
Microbial communities inhabiting intertidal sediment show diverse metabolisms to adapt to hydrodynamic conditions. However, the priming effect of exogenous organic matter on microbial metabolic fluxes remains poorly understood. Here we investigated microbial intercellular activities in surface sandy intertidal sediment (0–5 cm depth, from the Nanhui tidal flat, East China Sea) under anoxic conditions by incubating with position-specific 13 C labelled glucose isotopologues. Elevated production of 13 C-CO 2 and phospholipid-derived fatty acids (PLFAs) was observed after 96-hour incubation, suggesting a positive priming effect on both catabolic and anabolic activities. The different incorporations of 13 C-label from glucose isotopologues into CO 2 and PLFAs reveal distinct intracellular carbon fluxes through the central metabolic network. Specifically, microbial communities preferentially utilize the Embden-Meyerhof-Parnas (EMP) pathway (62% flux), followed by the Pentose Phosphate (PP, 25%) and Entner-Doudoroff (ED, 13%) pathways. These flux distributions closely mirror their corresponding functional genome proportion (55% EMP, 26% PP, 20% ED), suggesting a metabolic balance between energy yield and enzyme cost across glycolytic routes. Furthermore, metabolic flux analysis based on 13 C-PLFA profiles highlights diverse metabolic strategies among different microbial taxa, primarily involving the EMP, ED and tricarboxylic acid pathways. This underscores the dual importance of energy production and carbon allocation for biomass synthesis. Given the high protein cost for the EMP pathway, energy acquisition may be prioritized by anaerobes to withstand the fluctuating conditions. Our results suggest that microbial interactions with intercellular networks may play a critical role in facilitating the priming and subsequent degradation of sedimentary organic matter.